Wezwałem cię po numerze. 172364, 119198, 132434 i inni - Roszak, Joanna (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The title “I have called you by your number” is paraphrased from the book of Isaiah. In Torah the change of name of the main character suggests the turning point of his/her fate. In the article I concentrate on the gesture of assuming pseudonym-anagrams by a few poets – it is viable to read it as an attempt at self-determination, and as a painful dividing line, and as a form of a mask, and an analogue of a perturbed fate. My reflection concentrates on texts by Sachs, Domin, Celan, Amichai, Améry with a motif of numbers (the turned over analogues of the names) – I find a context in the poem by Wisława Szymborska Still; and in the performance by Raimund Hoghe, staged only once, just in Poland, entitled site specific; the project 80064 by Artur Żmijewski or works by Roman Opałka. The promise written in the Book of Isaiah of liberating Israel, which was supposed to be a work of God’s omnipotence, God talking to Jacob – who is an allegory of Israel: “Don’t be afraid, for I have redeemed you; I have called you by your name, you are mine. When you pass through the waters, I will be with you; and through the rivers, they shall not overflow you: when you walk through the fire, you shall not be burned, neither shall the flame kindle on you. For I am Yahweh your God”, in Auschwitz turned into the antithesis, and hence a threat that has a completely different sender than a good father: Be afraid, or else nobody will redeem you. I am calling you by the number, you are no one’s. You will go to the fire and a flame will consume you. You are alone.
I have called you by your number. 172364, 119198, 132434 and others